Investigating the use of internet marketing in the Singapore hotel industry. - Leong, Evangeline Qi Wen. (2008)
This research seeks to shed some light on the value of Internet marketing of hotels and its significance in the hotel industry in Singapore. On the basis of a survey of 301 hotel guests and interviews with 32 hotel executives, the research notes that while all the hotels already have some form of online presence, there are many potential marketing tools in the Internet marketing medium that they can look into. It is also found that Asians mainly prefer the use of 3rd party websites to make hotel room reservations.